Pelatihan Pemasangan Instalasi Listrik Tenaga Untuk Masyarakat Binaan Disnaker Di Pemkot Malang - Anang Dasa Novfowan; Mochammad Mieftah; Rachmat Sutjipto; Dhimas Kharisma; Sukamdi (Publisher UPT P2M Politeknik Negeri Malang, 2022)
Training on the correct, precise and safe installation of electric power installations for the people assisted by the Manpower Office in the Malang City Government. The existence of this training is expected to provide additional skills for installing power installations, to be used in working on installing power installations that are correct and safe and in accordance with standards, so as to minimize work hazards or accidents due to errors due to installation and use.